Transforming School Libraries in Madura to Support Students' Digital Literacy - Alfiatur Rahmania; Ahmad Arifandi; Ainur Rizalullah; Rusdiana Navlia (Penerbit Presisi Pustaka, 2026)
One of the important steps in responding to the development of information technology in the digital era is the transformation of school libraries. This study aims to examine the role of transforming school libraries in Madura in supporting students’ digital literacy. A literature review was conducted using a descriptive qualitative approach. The results indicate that digital libraries provide easier, more flexible, and more interactive access to information for students. In addition, digital libraries contribute to enhancing students’ critical, analytical, and creative thinking skills. However, in Madura, the implementation still faces several challenges, such as limited infrastructure, lack of human resources, and the digital divide. Therefore, to optimize the role of libraries as centers of digital literacy, innovative and locally grounded management strategies are required.